Inspirujący Anton Makarenko. Z analizy hieroglifów na „Dziełach” - Maria Groenwald (Problemy Wczesnej Edukacji)
In the paper “hieroglyphs” denotes (metaphorically) all meanings assigned by readers of texts comprising “Works” by A. Makarenko, thus designating highlighted fragments as meaningful. Their analysis has been directed at those issues that particularly appealed to the readers and the possibilities arising from them of applying knowledge to work with pupils. It turns out that while reading “Works” they focused on: (1) aims of upbringing and ways of fulfilling them: discipline, codes of conduct, collective group structure; (2) A. Makarenko himself, in whom they sought the ideal of a pedagogue. The analysis closes with a reflection on the role of the reader of “Works” as their peculiar translator who, through both reproductive and innovative work with the text (carried out through the prism of one’s own knowledge, experience or needs), enters the path of translating-interpreting pedagogical activity.